Local prevalence and transmission of avian malaria in the Alakai Plateau (Kauai, Hawaii, USA) - Glad, Anouk (2023)
Avian malaria is today one of the most important threats to native Hawaiian forest birds. Avian malaria is caused by the parasite Plasmodium relictum, which infects passerine red blood cells and is transmitted by the introduced mosquito vector Culex quinquefasciatus. Temperatures rises and precipitation declines due to climate change over the last decade may be responsible for the observed recent expansion in the range and prevalence of avian malaria on the Alakai Plateau, Kauai Island. To examine the hypothesis that conditions are now favorable for transmission of malaria on the Plateau, adult mosquitoes were sampled with CO2 traps and Reiter oviposition traps at three sites (Kawaikoi, Halepa’akai, and Koke’e) on several occasions between October 2013 and April 2014. P. relictum infection was assessed by PCR or dissection under a microscope. We surveyed also mosquito larvae along Halepa’akai and Kawaikoi streams. We observed that C. quinquefasciatus is well established on and near the Alakai Plateau, as mosquitoes were caught on all field trips, except in April at Halepa’akai, and larvae were found in all seasons. We observed differences in adult abundance among sites, seasons, and microhabitats (stream vs. ridge lines). However, malaria transmission on the Plateau may yet be restricted by the effect of cool temperatures on P. relictum development; as only one mosquito was found to be infected. Extensive field work, including surveys at Koke’e and in low elevation areas, is needed to better understand transmission mechanisms in the Alakai.